3(t+6)=-12

Simple and best practice solution for 3(t+6)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(t+6)=-12 equation:


Simplifying
3(t + 6) = -12

Reorder the terms:
3(6 + t) = -12
(6 * 3 + t * 3) = -12
(18 + 3t) = -12

Solving
18 + 3t = -12

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 3t = -12 + -18

Combine like terms: 18 + -18 = 0
0 + 3t = -12 + -18
3t = -12 + -18

Combine like terms: -12 + -18 = -30
3t = -30

Divide each side by '3'.
t = -10

Simplifying
t = -10

See similar equations:

| -5/3v-1/5=2/5v-7 | | 3x+12x-20=19x-4x+3 | | 7y-1=11+3 | | -10b-20=-20 | | 26+x=40 | | 2x^2-16x-58=0 | | 3sin(x)+4=1.57 | | 20x+4=10x-5 | | 1.50=.75b | | 20x+4=110x-5 | | 12x+x^2=225 | | X^4+7x^2-12=0 | | 3.5-0.5=26.0 | | 2n+2=-34 | | -26-x=40 | | 3x+30=30 | | (9+v)(5v-4)=0 | | -26+x=40 | | 3x/5-5=2 | | 27x-54=6x | | 56x+40y= | | 75y^3+90y^2+27y= | | 2-16x=0 | | f-1(x)=x^2+8x+2 | | (7x/4)-3=2y | | 13x+6+8x+6=180 | | 1000=1000-100a | | 2(x-5)=5(3x+9) | | 4/7-(x-5/51)=1/6 | | 12+7g=33 | | x+75+119+x=180 | | |[2x-12]/2|≤8 |

Equations solver categories